2020
DOI: 10.1101/2020.12.16.423122
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immune-Based Prediction of COVID-19 Severity and Chronicity Decoded Using Machine Learning

Abstract: Individuals with systemic symptoms long after COVID-19 has cleared represent approximately ~10% of all COVID-19 infected individuals. Here we present a bioinformatics approach to predict and model the phases of COVID so that effective treatment strategies can be devised and monitored. We investigated 144 individuals including normal individuals and patients spanning the COVID-19 disease continuum. We collected plasma and isolated PBMCs from 29 normal individuals, 26 individuals with mild-moderate COVID-19, 25 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Another important aspect is the permanency of S1-containing cells in the circulation, intermediate monocytes express high levels of CCR5 and extravasation of these cells can occur in response to CCL4 gradients. We showed that PASC individuals have low levels of CCL4 ( 5 ) maintaining these cells in circulation until they turn into nonclassical monocytes. Moreover, IFN-γ induced CX3CL1/Fractalkine production by endothelial cells ( 23 ) creates a gradient within the vascular compartment preserving nonclassical monocytes expressing CX3CR1 in the circulation.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Another important aspect is the permanency of S1-containing cells in the circulation, intermediate monocytes express high levels of CCR5 and extravasation of these cells can occur in response to CCL4 gradients. We showed that PASC individuals have low levels of CCL4 ( 5 ) maintaining these cells in circulation until they turn into nonclassical monocytes. Moreover, IFN-γ induced CX3CL1/Fractalkine production by endothelial cells ( 23 ) creates a gradient within the vascular compartment preserving nonclassical monocytes expressing CX3CR1 in the circulation.…”
Section: Discussionmentioning
confidence: 87%
“…During pathologic conditions mediated by infectious/inflammatory reactions, the proportions of monocyte subsets vary according to the functionality of each specific subpopulation ( 6,13,15 ). Our previous results show that during early stages of the disease, PASC group have reduced classical monocyte and increased intermediate monocyte percentages compared with healthy controls ( 5 ). We find an increase in nonclassical monocytes in PASC group 6-15 months post infection, and higher percentages of intermediate and nonclassical monocytes at day 0 in severe cases, suggesting augmented classical-intermediate-nonclassical monocyte transition in both groups but with different kinetics.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…• Recently, some studies has suggested that it is possible to identify the immunologic signatures of post-COVID-19 syndrome [60].…”
mentioning
confidence: 99%